Abordagem ergonômica da contribuição da fisioterapia para a melhoria da execução das atividades da vida diária pelos idosos portadores da doença de Parkinson - Almeida, Christiane Maria Azevedo de (2005)
The subject of this research is aging and the main degenerative diseases from the process with focus on Parkinson´s Disease. Through an ergonomic approach the contribution of physiotherapy in the improvement of daily life activities in elderly people with Parkinson is investigated. The importance of the environment in the maintenance of the functionality and the life quality of those old people was also studied. Using applied research theoretical referential and field observations one come to the conclusion that physiotherapy should contribute to ease the performance of daily life activities by old people with Parkinson´s Disease keeping their autonomy during a longer period of time. It become clear the benefit brought by the Pilates environment and the use of its techniques in the physiotherapeutic works aiming the improvement of daily life activities of elderly people. We hope that this study stimulates new researches which may contribute to the improvement of life quality of old people with Parkinson´s Disease